LITERATURE REVIEW ON CORE ASSESSMENT PRINCIPLES OF COMPETENCY BASED MEDICAL EDUCATION CBME (The Research of Medical Science Review, 2024)
The purpose of this study is to review the literature on competency-based medical education (CBME) principles and to identify some preventative strategies. Integrating competency-based medical education (CBME) into the standard curriculum is a significant difficulty. This study emphasize its practical implementation.